REVIEW: Antimicrobial resistance in wildlife. Issue 2 (April 2016) - Vittecoq, Marion; Godreuil, Sylvain; Prugnolle, Franck; Durand, Patrick; Brazier, Lionel; Renaud, Nicolas; Arnal, Audrey; Aberkane, Salim; Jean‐Pierre, Hélène; Gauthier‐Clerc, Michel; Thomas, Frédéric; Renaud, François
Summary: The spread of antimicrobial resistance is of major concern for human health and leads to growing economic costs. While it is increasingly hypothesized that wildlife could play an important role in antimicrobial‐resistant bacteria dynamics, empirical data remain scarce. The present work builds on a systematic review of the available data in order to highlight the main information we have and to suggest research pathways that should be followed if we aim to fill the gaps in our current knowledge. To achieve this goal, we address four questions: (i) Which resistant bacteria are the most frequently observed in wildlife? (ii) How are resistant bacteria exchanged between wildlife and the other hosts involved? (iii) In which habitats are those resistant bacteria found? (iv) Are resistances associated with certain ecological traits of the host? Synthesis and applications . We highlight the strong link existing between the impact of human activities on natural habitats and the carriage of antimicrobial‐resistant bacteria by wildlife. Furthermore, we underline that omnivorous, anthropophilic and carnivorous species are at high risk of being carriers and potentially spreaders of antimicrobial‐resistant bacteria. Identifying among those groups key sentinel species may be of particular interest to implement ecosystem contamination surveillance. Finally, we discuss possible exchange routes for antimicrobial‐resistant bacteria between humans and wildlife. Considering that water is of major importance in those exchanges, a critical way to control antimicrobial resistance spread may be to limit aquatic environment contamination by antimicrobial‐resistant bacteria and antibiotics. Abstract : We highlight the strong link existing between the impact of human activities on natural habitats and the carriage of antimicrobial‐resistant bacteria by wildlife. Furthermore, we underline that omnivorous, anthropophilic and carnivorous species are at high risk of being carriers and potentially spreaders of antimicrobial‐resistant bacteria. Identifying among those groups key sentinel species may be of particular interest to implement ecosystem contamination surveillance. Finally, we discuss possible exchange routes for antimicrobial‐resistant bacteria between humans and wildlife. Considering that water is of major importance in those exchanges, a critical way to control antimicrobial resistance spread may be to limit aquatic environment contamination by antimicrobial‐resistant bacteria and antibiotics.